Successes and failures of knowledge management - Liebowitz, Jay, 1957- (Morgan Kaufmann is an imprint of Elsevier, 2016)
Successes and Failures of Knowledge Management highlights examples from across multiple industries, demonstrating where the practice has been implemented well-and not so well-so others can learn from these cases during their knowledge management journey. Knowledge management deals with how best to leverage knowledge both internally and externally in organizations to improve decision-making and facilitate knowledge capture and sharing. It is a critical part of an organization's fabric, and can be used to increase innovation, improve organizational internal and external effectiveness, build the institutional memory, and enhance organizational agility. Starting by establishing KM processes, measures, and metrics, the book highlights ways to be successful in knowledge management institutionalization through learning from sample mistakes and successes. Whether an organization is already implementing KM or has been reluctant to do so, the ideas presented will stimulate the application of knowledge management as part of a human capital strategy in any organization.